Emotional Relations with Environment as Assessed by Pupils - Stulpinas, Tomas (Acta Paedagogica Vilnensia, 2001)
The aspects of fear, sympathy, tendency of belief, the most important and reliable ones, perception of perfectness and necessity of solitude were stated by the questionnaire of 3927 3-rd formers. The pupils’ emotional and evaluating attitudes are most associated with the closest environment. The assessed emotional relations are influenced by the age of the respondent, their gender and place of residence.